MICROZONATION ANALYSIS IN MANNA CITY & PASAR MANNA SUBDISTRICTS UTILIZING MICROTREMOR DATA, SOUTH BENGKULU REGENCY - Refrizon, Refrizon; Fadli, Darmawan Ikhlas; Triutami, Olga; Putri, Aisyah Cindy Phylia; Rahmawati, Nurul Ilmi (Universitas Mataram, 2024)
South Bengkulu is prone to earthquakes because it is located on the Great Sumatran Fault. Apart from that, it is also influenced by the activity of the Musi and Manna segments, so that besides being influenced by the two active tectonic plates it is also influenced by the local segment. This research is located in Manna City and Manna Market, which is mostly inhabited by people and is the capital of South Bengkulu. In connection with infrastructure development, it is necessary to know the condition of the soil layers to minimize the risk of building damage due to earthquakes. This research aims to analyze earthquake-prone areas based on dominant frequency parameters, soil amplification, seismic vulnerability index and sediment layer thickness (h). Research data comes from microtremor measurements at 60 measuring station points in Manna City and Manna Market. The tool used is a Short Period Portable Seismometer Model Gemini 2 SN-1405. This microtremor data is processed using the Horizontal to Vertical Spectral Ratio (HVSR) method. The results of data processing show that the research area has the lowest dominant frequency of 3.95 Hz and the highest of 49.71 Hz. The ground vibration amplification value is classified as small to medium, the lowest is 1.3 and the highest is 5.19. The lowest earthquake vulnerability index was 0.18 cm2/s and the highest was 2.24 cm2/s. The smallest sediment thickness was 3.77 meters and the thickest was 47.48 meters. From the results of the calculation of the seismic vulnerability index in Kota Manna and Pasar Manna Districts, the seismic vulnerability index value is relatively small, in accordance with the amplification factor and the thickness of the sediment layer. Based on this research, although Manna City and Manna Market are often shaken by earthquakes, the earthquake vibrations experience small amplification.